Interaction Between ITM2B and GLUT9 Links Urate Transport to Neurodegenerative Disorders - Mandal, Asim K.; Mount, David B. (Frontiers in Physiology, 2019)
Hyperuricemia plays a critical causative role in gout. In contrast, hyperuricemia has a protective effect in neurodegenerative disorders, including Alzheimer’s Disease. Genetic variation in the SLC2A9 gene, encoding the urate transporter GLUT9, exerts the largest single-gene effect on serum uric acid (SUA). We report here the identification of two GLUT9-interacting proteins, integral membrane protein 2B (ITM2B) and transmembrane protein 85 (TMEM85), isolated from a hman kidney cDNA library using the dual-membrane yeast two-hybrid system. ITM2B is a ubiquitously expressed, N-glycosylated transmembrane regulatory protein, involved in familial dementias and retinal dystrophy; the function of TMEM85 is less defined. Using coimmunoprecipitation, we confirmed the physical interaction between ITM2B or TMEM85 and N-terminal GLUT9 isoforms (GLUT9a and GLUT9b) in transfected HEK 293T cells and Xenopus oocytes, wherein ITM2B but not TMEM85 inhibited GLUT9-mediated urate uptake. Additionally, co-expression of ITM2B with GLUT9 in oocytes inhibited N-glycosylation of GLUT9a more than GLUT9b and stimulated urate efflux by both isoforms. However, urate uptake by N-glycosylation and N-terminal deletion GLUT9 mutants was efficiently inhibited by ITM2B, indicating that neither N-glycosylation nor the N terminus is necessary for functional interaction of GLUT9 with ITM2B. Notably, ITM2B variants linked to familial Danish dementia and retinal dystrophy significantly attenuated the inhibition of GLUT9–mediated urate influx. We propose ITM2B as a potential regulatory link between urate homeostasis and neurodegenerative disorders.